Stakeholder participation and crisis- responsive strategies in the Mediterranean blue bioeconomy-insights from Lebanon under Co-Evolve4BG project - Nahed Msayleb; Nada Mallah Boustani; Sana Abidib; Khouloud Athiman; Béchir Bejaoui (Frontiers in Marine Science)
IntroductionThis study investigates the long-term impacts of health emergencies—specifically the COVID-19 pandemic—on coastal tourism systems across the Mediterranean, with a particular focus on the Batroun pilot site in Lebanon. Coastal areas are especially vulnerable to systemic disruptions due to their dependence on tourism, ecological fragility, and governance fragmentation. Understanding how crises like COVID-19 reshape tourism dynamics is critical for advancing sustainable and resilient development within the blue bioeconomy framework.MethodsWe adopted a participatory research approach involving multi-stakeholder workshops, focus groups, and SWOT analyses. The Co-Evolve4BG Toolkit, a participatory evaluation instrument, was applied to assess the sustainability performance of Batroun's coastal tourism sector across environmental, economic, and governance dimensions. Thresholds and indicator scoring were co-developed with local actors and experts to reflect contextual realities.ResultsFindings revealed both systemic vulnerabilities and adaptive capacities. Batroun demonstrated relative strengths in public engagement, wastewater infrastructure, and cultural asset preservation. However, significant weaknesses emerged in pollution management, marine habitat protection, and institutional coordination. The COVID-19 pandemic acted as a stress test, highlighting the fragility of current systems but also catalyzing shifts toward digital tourism, circular economy initiatives, and decentralized decision-making.DiscussionThe Co-Evolve4BG Toolkit proved to be an effective mechanism for benchmarking sustainability and co-developing locally grounded action plans. Insights from the Batroun case emphasize the importance of participatory governance and integrated coastal management in building long-term resilience. We recommend the adoption of standardized health protocols, diversification of tourism models, and improved inter-institutional coordination at the regional level. These findings contribute to a replicable model for aligning ecological preservation with crisis-responsive tourism planning in Mediterranean coastal areas.